2014
DOI: 10.1590/s0034-737x2014000300018
|View full text |Cite
|
Sign up to set email alerts
|

Spacing, population density and nitrogen fertilization in corn grown in an Oxisoil

Abstract: RESUMOEspaçamento, densidade populacional e adubação nitrogenada na cultura do milho O objetivo deste trabalho foi avaliar os componentes de produção, teor de nitrogênio (N) no tecido foliar e produtividade de grãos na cultura do milho em função de diferentes espaçamentos entre linhas, densidade populacional e doses de adubação nitrogenada em cobertura. O experimento foi conduzido no município de Toledo-PR, no ano agrícola de 2005/2006, em área de Latossolo Vermelho Eutroférrico sob sistema de semeadura direta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
4
5
0
1
Order By: Relevance
“…Higher grain yields have also been observed in other studies conducted using interrow spacing of 0.90 m (Kappes et al, 2014;Lana et al, 2014).…”
Section: Resultssupporting
confidence: 74%
“…Higher grain yields have also been observed in other studies conducted using interrow spacing of 0.90 m (Kappes et al, 2014;Lana et al, 2014).…”
Section: Resultssupporting
confidence: 74%
“…However, they presented differences in relation to organic fertilization. These results corroborate with Lana, Rampim, Ohland, and Fávero (2014b), verifying that organomineral fertilization provided the same productivity of corn. However, Rodrigues et al (2012) found that the use of organomineral fertilization based on humus did not provide higher productivity in the corn crop than the mineral source, however, the organic source was more cost-effective than organomineral and mineral sources.…”
Section: Treatmsupporting
confidence: 84%
“…A produtividade do milho está relacionada com a redução do espaçamento entrelinhas, utilização de híbridos mais produtivos e densidade populacional adequada (Argenta et al, 2001;Silva et al, 2014;Lana et al, 2014). Segundo Argenta et al (2001), híbridos mais precoces respondem melhor à distribuição mais regular de plantas, aumentando seu potencial produtivo de grãos.…”
unclassified